STRATEGI KOMISI PEMILIHAN UMUM KABUPATEN TULANG BAWANG BARAT DALAM MENINGKATKAN PARTISIPASI PEMILIH DISABILITAS PADA PEMILU TAHUN 2024 - dina, Bella; Belladina, B; Akhyar, Taufik; Darmawan, Erik (Jurnal Studi Ilmu Politik, 2025)
The General Election Commission is one of the election organizing institutions. The problem with this research is the low level of participation of disabled voters in the 2019 elections. Therefore, this research aims to find out what strategies are being implemented by the West Tulang Bawang KPU in increasing the participation of disabled voters in the 2024 elections. The method used is a qualitative approach with the type field research. Meanwhile, data collection techniques were carried out using observation, interviews and documentation. In analyzing research using strategy theory according to Schendel and Charles Hofer (1985). The results of this research show that in increasing the participation of voters with disabilities in the 2024 elections, the West Tulang Bawang KPU implemented a strategy with four levels or stages, namely: First, Enterprise Strategy related to the role of the KPU as an organization that has relationships with the community. Second, the Corporate Strategy of the West Tulang Bawang KPU carries out strategies related to its vision and mission and function as an election organizing institution. Third, Business Strategy as a strategy at the KPU level as an election organizing institution to attract participation from voters with disabilities in the community with demand and support. Fourth, the Functional Strategy of the West Tulang Bawang KPU by conducting elections door to door or visiting the residences of people with disabilities who cannot attend the polling location due to accessibility problems.